2020
DOI: 10.29121/granthaalayah.v8.i8.2020.435
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antimicrobial Analyses of Leaf Extracts of Cerathoteca Sesamoides and Chromolaena Odorata

Abstract: It was reported in 2005 during WHO survey that about 70-80% of the world population use medicinal plants either in their crude unmodified form or partially in their modified semi-synthetic form of plant sources in their primary healthcare. The present study investigated the phytochemicals and antimicrobial activities of the leaf extracts of Cerathoteca sesamoides and Chromolaena odorata to ascertain their potentials in herbal medicine. Fresh leaf of the plants obtained from Lafia in Nasarawa State, Nigeria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Although the composition of rumen microbes was not measured in this study, the reduction in the molar proportion of C 2 equivalent VFAs suggested that the increasing level of chromolaena induced the growth and fermentation process of propionate-producing rumen microbes. A more realistic proposition is that various secondary metabolite/s in the chromolaena (Kato-Noguchi & Kato, 2023) meal might be the cause since Abubakar et al (2020) reported a significant antibacterial activity of chromolaena extract. Up to now, there have been no reports on the effects of C. odorata on rumen microbes, creating a knowledge gap regarding how the inclusion of chromolaena alters the rumen microbial ecosystem.…”
Section: Becausementioning
confidence: 99%
“…Although the composition of rumen microbes was not measured in this study, the reduction in the molar proportion of C 2 equivalent VFAs suggested that the increasing level of chromolaena induced the growth and fermentation process of propionate-producing rumen microbes. A more realistic proposition is that various secondary metabolite/s in the chromolaena (Kato-Noguchi & Kato, 2023) meal might be the cause since Abubakar et al (2020) reported a significant antibacterial activity of chromolaena extract. Up to now, there have been no reports on the effects of C. odorata on rumen microbes, creating a knowledge gap regarding how the inclusion of chromolaena alters the rumen microbial ecosystem.…”
Section: Becausementioning
confidence: 99%